The Effect of Occupational Safety and Health on Employee Work Productivity - Sattar, Sattar; Minhani, Minhani; Khotimah, Ramdiyah Nurul (Bulletin of Science Education, 2021)
The purpose of this study was to determine the effect of occupational safety and health on work productivity of employees at PT. Cipta Sumina Indah Satresna Samarinda. This study uses two independent variables, namely safety and health with one dependent variable, namely employee productivity. After reviewing the literature and the field and formulating hypotheses, the data in this study were collected through distributing questionnaires to 54 employees at PT. Cipta Sumina Indah Satresna as the research sample. The sampling technique used is purposive sampling. The data analysis method used is quantitative analysis, namely validity, reliability, multiple linear regression analysis, f test, t test, and coefficient of determination. From the results of the analysis of the discussion carried out by the author, the results of the study show that the indicators in this study are valid and reliable. Keywords: Occupational Safety, Work Productivity, Employee Work Productivity